QUANTUM CHEMICAL MODELING OF THE TYPE OF COORDINATION OF MANGANESE WITH VITAMIN B2 AND ESSENTIAL AMINO ACIDS - A. A. Gvozdenko; M. A. Pirogov; A. V. Blinov; Al. B. Golik; A. A. Yakovenko; A. A. Blinova (Современная наука и инновации)
Within the framework of this study, quantum chemical modeling of the type of coordination of manganese with vitamin B2 and essential amino acids was carried out. The interaction of manganese with amino acids was carried out through the carboxyl group and amino group of the amino acid, interaction with vitamin B2 was carried out through various pairs of enolic oxygen and a neighboring nitrogen heteroatom. As a result of modeling, it was found that all the presented interactions are energetically favorable (∆E ≥ 2331,756 kcal/mol) and chemically stable (η ≥ 0.096 eV). The coordination of manganese with vitamin B2 and essential amino acids occurs through N3 and enolic oxygen attached to the C2 atom in the pyrimidine ring of vitamin B2, and through the carboxyl group and amino group attached to the C2 atom of amino acids.